Answer:
the simplified expression is negative twelve sevenths
Explanation:
To simplify the expression, we can start by applying the rules for combining like terms:
(-7) * 2 - (3 * sqrt(64)) = (-14) - (3 * sqrt(64))
Next, we can use the fact that the square root of 64 is 8 to simplify the expression further:
(-14) - (3 * sqrt(64)) = (-14) - (3 * 8) = (-14) - 24 = -38
Finally, we can simplify the fraction by dividing the numerator and denominator by their greatest common factor:
-38 / 5 = (-38 / 2) / (5 / 2) = -19 / 2 = negative twelve sevenths
Therefore, the simplified expression is negative twelve sevenths.